MODEL ARSITEKTUR POHON PADA HULU DAS CIANJUR ZONA SUB-MONTANA TAMAN NASIONAL GUNUNG GEDE PANGRANGO - Arrijani; Boy J.A Lombok (LPPM Universitas Terbuka, 2006)
Tree architectural model represents one of the important concepts to quip characteristic takson in plant morphology and plant taxonomic. Every tree grows at the watershed has a typical architectural model and different ability in rainfall transformation such as stemflow, throughfall, and interception. This research explores tree architectural models at upstream Cianjur watersheds in Mt. Gede Pangrango National Park. Sampling conducted by using plot method to chose 15 trees at sub-montana zone to measure IVI and elevation bevel. Results of the research indicate that there are 12 tree architectural models at upstream Cianjur watersheds. At sub-montana and montana zone models the architectural models are ATTIMS (1 sp), FAGERLIND (1 sp), KWAN-KORIBA (1 sp), MASART (1 sp), PETIT (3 sp) PREVOST (2 sp), RAUH (2 sp), ROUX (1 sp), SCARRONE (1 sp), STONE (1 sp,) and THEORETICAL I (1 sp).